(untitled) (Damascus University Journal of Historical Studies, 2024)
The Association of Algerian Scholars was founded in the year 1931 AD, under the French occupation of Algeria, and included in its ranks some Algerians from Algeria, and fighting the policy of integrating Algeria into France, Arab education, the United Arab Emirates, the founder of the association, and the discussion took place around three personalities: Abdel Hamid bin Badis Ahmed Tawfiq Al-Madani, and merchant Omar Ismail. The importance of the research comes from the importance of the Association of Scholars, which was the most important leading association among the political parties in Algeria, and the importance of the stage of its establishment. The opinions that revolved around the founder of the Association of Scholars, and the study ended with a set of results, the most important of which is that the establishment of a party that unites the scholars was the talk of the people, Which Ibn Badis sought to form since 1913 AD, and following the initiative taken by Mr. Omar Ismail in the year 1931 AD, this party was founded, represented by the Association of Scholars, after he suggested to Abdel Hamid bin Badis to establish this party in 1931 AD.